The Law on Earth, or the Importance of the Beginning of the Land Border to Define Maritime Borders. The Case between Peru and Chile - Novak Talavera, Fabián (2008)
This paper develops the importance of the delimitation of the point of beginning of the terrestrial border to define the maritime borders; in addition, it determines the location of this point in the case of the border between Peru and Chile, which, in turn, initiates the maritime border of the same. In this sense, the author develops, first, the analysis of the Treaty and Supplementary Protocol to resolve the issue of Tacna and Arica of 1929 and the demarcation made by the Mixed Boundary Commission between Peru and Chile in 1930. two ideas conclude: i) in the face of disagreements between the delegates of both countries during the demarcation, it is the governments of both States that directly solve these discrepancies and ii) according to the treaty of 1929 and the demarcation made in 1930, it is the Concordia which starts the land border. Secondly, it analyzes the Chilean position with respect to the Treaty and Complementary Protocol to resolve the issue of Tacna and Arica, specifically, the position it adopts since 2001 regarding the beginning of the land border. Indeed, Chile, since 2001, claims that the beginning of the land boundary is Milestone No. 1. It is necessary to mention that this new position contradicts the principles of international law, such as the principle pacta sunt servanda, the principle of good faith, among others. In the third place, the author establishes the consequences of the Chilean thesis, since this generates legal as well as geographical absurdities, such as the formation of a "dry coast". Finally, the starting point of the land border between Peru and Chile is established, which is followed by the Treaty to resolve the issue of Tacna and Arica, and what is its relevance in the delimitation of the maritime border of those countries.